1997
DOI: 10.1258/0956462971919886
|View full text |Cite
|
Sign up to set email alerts
|

Infection with HIV, syphilis and hepatitis B in Ethiopia: a survey in blood donors

Abstract: Sera of all male donors appearing at the blood bank of a regional hospital in Northwest Ethiopia in 1994 (n = 1022) and 1995 (n = 1164), were screened for the presence of human immunodeficiency virus (HIV-1) and treponemal antibodies. Additionally, screening for hepatitis B surface antigen (HBsAg) was carried out on 549 consecutive sera. In 1995, the crude seroprevalence of HIV-1 infection and syphilis was 16.7% and 12.8%. Seroprevalence of HBsAg was 14.4%. HIV and syphilis seroprevalence was highest in soldie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
4
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 2 publications
5
33
4
1
Order By: Relevance
“…A study of HBsAg carrier pregnant women in Addis Ababa [28] provided direct evidence of the low risk of perinatal transmission. Whilst estimates of HBsAg prevalence of 10-14% and seroprevalence of 76-79% for Ethiopian adults [9,20,24,27] appear higher than those observed in this study, the low precision of prevalence estimates in some of the earlier studies, and differences between studies in age representations and sampling criteria, make quantitative comparison difficult. Regional differences in HBV marker prevalence are observed in Ethiopia [9,20,24], which might affect prevalence in Addis Ababa in view of the considerable inmigration over the past 20 years.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…A study of HBsAg carrier pregnant women in Addis Ababa [28] provided direct evidence of the low risk of perinatal transmission. Whilst estimates of HBsAg prevalence of 10-14% and seroprevalence of 76-79% for Ethiopian adults [9,20,24,27] appear higher than those observed in this study, the low precision of prevalence estimates in some of the earlier studies, and differences between studies in age representations and sampling criteria, make quantitative comparison difficult. Regional differences in HBV marker prevalence are observed in Ethiopia [9,20,24], which might affect prevalence in Addis Ababa in view of the considerable inmigration over the past 20 years.…”
Section: Discussioncontrasting
confidence: 79%
“…3 %, and in male blood donors in NW Ethiopia HBsAg prevalence was reported as 14 . 4% [24]. A study of HBsAg carrier pregnant women in Addis Ababa [28] provided direct evidence of the low risk of perinatal transmission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate was comparable to that reported from Lucknow 2.2% (5) , North India 2.5% (25) , Mumbai 2.02% (9) , Pakistan 2.21% (24) , Calcutta 2.8% (4) and Bangladesh 2.4% (17) . When the results of the present study was compared with those reported from similar blood donors of other countries like Cameroon 11.72% (35) , Taiwan 4.5% (32) , Ethiopia 14.4% (27) , Mauritania 20.3% (20) , Thailand 4.51% (21) , Djibouti 10.4% (8) , Mangolia 8.2% (33) , this study showed relatively lower prevalence of the hepatitis-B surface antigen whereas countries like Brazil 1.9% (23) , Iran 1.07% (12) , Turkey1.5% (28) and US Community 0.15% (18) , showed lower HBsAg positivity in comparison to the present study.…”
Section: Discussionmentioning
confidence: 62%